TEACHER LOOKS ON ADOLESCENCES - Ponce-Grima, Víctor M. (2019)
This work is an advance research participatory action around the emotional health of teachers. The study starts from the teachers' view of themselves and their students, adolescents, of secondary schools in the periphery of Guadalajara. The research is part of a coexistence project that aims to heal the school tissues that are significantly harming the educational development of adolescents on the outskirts of Guadalajara. For years the reduction of the capacity to educate / socialize has been announced both by the school and by the family. This precariousness significantly affects identity, self-esteem and dangerous life projects. With this precarious assistance to adolescents to secondary school (Ponce, Torres and Ropero 2019), who attend school to socialize, to complete the gaps in family socialization (Tenti, 2012). Relationships between adolescents, from these precariousnesses, are usually violent towards them or between them. These are increasing (Prieto, 2017), in turn, teenagers' relationships with their teachers have deteriorated (Torres and Ponce, 2017 and 2018). After various difficulties, it is clear that the violence is not easy to deal with, the forms of intervention are analyzed, which far from favoring exacerbate the problems. Some intervention proposals are: 1) The collaborative accompaniment of the internal agencies of the schools. 2) The conformation of new forms of relationship, where we overcome vertical relationships, or relationships where the formator shapes. 3) The practice of basic values, such as respectful listening, the recognition of the other and mutual learning. The main purpose of the strategy is to meet with school groups and practice active listening and reflective dialogue. Subsequently, work projects that participate in the demands of school groups would be built. During the first visits, reflection exercises are carried out around three main movements: how I feel, how I interact with my colleagues, and what I know of my students and how I interact with them. In this work, the analyzes and interpretations of the teachers' stories about which students and how they relate to adolescents, their students, are made known. In the end, we realize that the stories are not homogeneous. Two extreme positions are recognized from the heterogeneity: those who recognize that they do not know and do not get along with students; and those who affirm that they have approached their students, and this has caused them sympathy around their sufferings. The highlight of this exercise is that while everyone brings a narration of their world, to the dialogue around common problems, we realize that they share similar frustrations about their experiences.